Work function variations on electrostatic and RF performances of JLSDGM Device - K K. E. Kaharudin; F. Salehuddin; A. S. M. Zain; Ameer F. Roslan; I Ahmad (Institute of Advanced Engineering and Science, 2021)
This paper offers a systematic analysis on the impact of work function (WF) variations on electrostatic and radio frequency (RF) performances of nchannel junctionless strained double gate (DG) (n-JLSDGM) metal oxide semiconductor field effect transistor (MOSFET). The study has been performed under othe constant level of design parameters that operates in saturation as a transconductance amplifier, considering the dependence of electrostatic and RF performance on the variation of WF. Furthermore, this paper aims to provide physical insight into the improved electrostatic and RF performances of the proposed n-JLSDGM device. The device layout and characteristics were designed and extracted respectively via a comprehensive 2-D simulation. Device performances such as on-state current (ION), off-state current (IOFF), on-off current ratio, subthreshold swing (SS), intrinsic capacitances, dynamic power dissipation (Pdyn), cut-off frequency (fT) and maximum oscillation frequency (fmax) are intensively investigated in conjunction with WF variations.